Transcatheter aortic valve thrombosis: Data from a French multicenter cohort analysis. Issue 2 (21st February 2021) - Mouyen, Thomas; Manigold, Thibaut; Collet, Jean‐Philippe; Durand, Eric; Barbey, Christophe; Lhermusier, Thibault; Tchetche, Didier; Chollet, Thomas; Mulliez, Aurélien; Motreff, Pascal; Combaret, Nicolas; Souteyrand, Géraud
Abstract: Objectives: To evaluate the effectiveness of anticoagulant therapies in patients with clinical transcatheter heart valve (THV) thrombosis, to describe complications, and to assess their risk profile was the objectives. Background: Little research has been conducted on clinical THV thrombosis. Methods: Patients with clinical THV thrombosis were identified based on greater than 50% increased transvalvular gradient on transthoracic echocardiogram confirmed by 4‐dimensional computed tomography, transesophageal echocardiogram, or regression with anticoagulant therapy. A cohort free from thrombosis for more than 1, 100 days postprocedure was used for comparison. Results: Fifty‐four patients with clinical THV thrombosis were identified. Most subjects (98.1%) received anticoagulant therapy which was effective (≥50% reduction in transvalvular gradient or return to postprocedure value) in 96%. The rate of serious hemodynamic or embolic complications in the thrombosis population was 31.5%. A multivariate analysis of subjects with and without thrombosis indicated a significantly increased risk of thrombosis from preexisting thrombocytopenia (odds ratio [OR] 9.96), absence of predilatation (OR = 5.67), renal insufficiency (OR = 4.84), and >10 mmHg mean transvalvular gradient postprocedure (OR = 3.36). No recurrence of thrombosis was identified during on average 685 days follow‐up. Conclusions: These data, from one of the largest cohorts with clinical THV thrombosis confirm anticoagulants appear effective. The rate of serious associated complications was high. The findings underline the importance of recognizing risk factors for thrombosis.